Peculiarities of respiratory functions in qualified swimmers exposed to multidirectional physical loads - Bolotin, A.; Bakayev, V.; Ponimasov, O.; Vasilyeva, V. (Journal of Human Sport & Exercise, 2022)
The peculiarities of the swimmers` respiratory system response to a special physical load were studied. The swimmers of high sports qualification aged 16-18 years old, who specialize in swimming at distances of various lengths, underwent the examination. At the first stage, we used exercises aimed at enhancing the anaerobic work power in swimming. At the second stage, the parameters of the swimmers` respiratory system response to the load in aerobic and anaerobic zone were studied. At the third stage of the study, the changes of the swimmers` respiratory functions under physical loads at the level of MOC (maximum oxygen consumption) were researched. The investigation of respiratory system functions of stayer swimmers was conducted with the use of a Spirolab-3 spirometer (spirograph). We found that the recovery of qualified swimmers can be activated when aerobic and anaerobic mechanisms of energy metabolism are combined. The results of the study confirm that the swimmers` respiratory functions influence the processes of recovery of their working capacity after being exposed to multidirectional physical loads. The sprinters` anaerobic mechanisms of muscle function are better developed. The stayers` aerobic mechanisms of energy metabolism function better. In order to activate the recovery of qualified swimmers, it is advisable to combine aerobic and anaerobic mechanisms of energy metabolism.